Attribution of blame to rape victims and offenders, and attribution of severity in rape cases: Non-therapists and survivor and offender therapists - Idisis, Yael (International review of victimology, 2017)
This article examines Wolf’s hypothesis of modular judgment in the context of rape myths and attribution of blame to rape victims. Modular judgment was operationalized using blame schemata suited to judgment of everyday aggression. Each of 88 female participants, of whom 29 were sexual trauma survivor therapists, 29 were sex offender therapists and 30 were non-therapists, was presented with written descriptions of 16 rapes, which included information regarding the victim’s behaviors before (her prior sexual experience), during (the kind and the degree of the resistance she exhibited) and after the rape (meeting or not meeting with the attacker). Dependent variables were attribution of blame to the survivor, attribution of blame to the attacker and judgments regarding severity of the rape. As expected, the therapists attributed less blame to the survivors and more blame to the attacker, and judged the rapes as slightly more severe than did non-therapist participants. For all participants in this study, the survivor’s behavior after the rape carried the greatest weight regarding attribution of responsibility to her. These results are discussed in terms of the theories of modular judgment and defensive attribution, and the just world theory. We recommend further investigations with regard to the perceived connection between survivors’ behaviors after a rape and blame attribution.